Soil carbon and nutrient (NPK) content in the tropical shifting cultivation system under indigenous agricultural management practices: a review - Mandah, V.P.; Tematio, P.; Onana, A.A.; Fiaboe, K.; Arthur, E.; Giweta, M.; Ndango, R.; Silatsa, F.B.T.; Biloa, J.B.; Masso, C. (2025)
Farmers largely depend on the soil's natural fertility in the shifting cultivation system, using minimal or no external agricultural inputs, and rely on slash-and-burn to clear fields due to limited resources. This system follows a cycle involving conversion, cultivation, and restoration phases, where various indigenous practices are applied, influencing soil nutrient dynamics positively and negatively. Significant efforts have been made to examine the relationship between soil organic carbon, nutrients (nitrogen, phosphorus, and potassium), and indigenous agricultural practices in tropical shifting cultivation. The findings from these studies need to be assessed to improve understanding and better inform decision-making. This review consolidates these results, emphasizing the status, similarities, controversies, and knowledge gaps. Overall, practices in shifting cultivation tend to have long-term negative impacts on soil fertility, requiring an extended recovery period. Unfortunately, tropical lands are experiencing shortening fallow periods. However, agroforestry has been identified as an alternative to enhance the resilience of affected lands offering additional benefits for soil fertility. Crop rotation, mixed cropping, minimum tillage, cover crops, and incorporating crop residues can also improve soil fertility by increasing soil organic carbon and nutrient levels. Therefore, promoting knowledge exchange with indigenous farmers can contribute to more agroecological resilient farming systems.